2012
DOI: 10.1007/s00520-012-1564-y
|View full text |Cite
|
Sign up to set email alerts
|

Concepts and definitions for “supportive care,” “best supportive care,” “palliative care,” and “hospice care” in the published literature, dictionaries, and textbooks

Abstract: Purpose Commonly used terms such as “supportive care,” “best supportive care,” “palliative care,” and “hospice care” were rarely and inconsistently defined in the palliative oncology literature. We conducted a systematic review of the literature to further identify concepts and definitions for these terms. Methods We searched MEDLINE, PsycInfo, EMBASE, and CINAHL for published peer-reviewed articles from 1948 to 2011 that conceptualized, defined, or examined these terms. Two researchers independently reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(146 citation statements)
references
References 46 publications
1
142
0
3
Order By: Relevance
“…4 Supportive care is defined as “the provision of the necessary services for those living with or affected by cancer to meet their informational, emotional, spiritual, social or physical need during their diagnostic treatment or follow-up phases encompassing issues of health promotion and prevention, survivorship, palliation and bereavement.” 120 Palliative care is supportive care for patients with advanced-stage disease, and includes interventional programmes used in both acute-care hospitals and the community. Hospice care is a form of community-based palliative care predominantly serving patients and their loved-ones at the end of life.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…4 Supportive care is defined as “the provision of the necessary services for those living with or affected by cancer to meet their informational, emotional, spiritual, social or physical need during their diagnostic treatment or follow-up phases encompassing issues of health promotion and prevention, survivorship, palliation and bereavement.” 120 Palliative care is supportive care for patients with advanced-stage disease, and includes interventional programmes used in both acute-care hospitals and the community. Hospice care is a form of community-based palliative care predominantly serving patients and their loved-ones at the end of life.…”
Section: Figurementioning
confidence: 99%
“…Considerable overlaps in the aims and approaches of ‘supportive care’, ‘palliative care’, and ‘hospice care’ have been recognized (Figure 1), and we previously identified the similarities and differences between these terms through a systematic review of the literature. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Growing from the hospice movement, today’s palliative care still mainly covers cancer, but also includes conditions such as HIV/AIDS, degenerative neurological disorders, heart conditions, liver and renal failure and brain injuries, for instance due to stroke 10. A systematic literature review on the concept of palliative care published in 2013 concluded that, ‘Although all definitions unanimously agreed that Palliative care serves patients with life-limiting illness, there has been some debate whether it involves patients with curable disease as well’ 15. A similar finding was derived in a concept analysis by Meghani in 2003, stating that ‘The scope of palliative care has evolved to include a wide range of patient populations who may not be appropriately termed “dying” but for whom alleviation of suffering and improvement of quality of life may be very relevant goals’ 11.…”
Section: The Who Definition Of Palliative Carementioning
confidence: 99%
“…The concept of palliative care for the terminally ill and the dying (which we refer to as “hospice care” [11]) encompasses various aspects. In the EoL care continuum, it comprises two meaningful episodes: the patient’s last months/weeks of life and the actual transition from life to death, the latter being a critical period of hours up to a week.…”
Section: Introductionmentioning
confidence: 99%